Bridging the Integration Deficit: Developing an Integrated Psychosocial-Financial Health Model for Buy Now, Pay Later Adoption - Ashri Putri Rahadi (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
The rapid expansion of Buy Now, Pay Later (BNPL) services has transformed digital finance, yet current scholarship remains siloed in its evaluation of consumer behavior. This systematic literature review addresses the "Integration Deficit" by synthesizing evidence across five critical dimensions: saving, budgeting, spending, borrowing, and investing. Adhering to the eight-step framework by Xiao & Watson (2019), a corpus of 31 peer-reviewed articles was analyzed using thematic synthesis. The findings reveal that BNPL adoption is driven by a complex interplay of cognitive biases—such as present bias and price focalism—and psychosocial catalysts like Fear of Missing Out (FoMO), which frequently override rational financial self-regulation. Crucially, this review moves beyond descriptive summaries to propose an Integrated Psychosocial-Financial Health Model. This framework operationalizes internal psychological states into quantifiable digital proxies, including repayment frequency and browsing diversity, to enhance creditworthiness assessments for "credit-invisible" young adults. The results highlight that digital financial literacy serves as a vital firebreak against unsustainable debt stacking and financial fragility. This study contributes actionable insights for fintech providers and regulators to foster ethical lending and sustainable financial well-being in an increasingly volatile digital economy.